Aerodynamic loads of a steady gliding grey-headed albatross - Janine Schoombie (2024)
This data contributed to the PhD thesis titled "Investigating aerodynamic factors in wind-driven grey-headed albatross crash-landings". The work looked into the fine scale wind vectors on Marion Island and the impact that has on fatal crash-landings in grey-headed albatrosses. The dataset given is an Excel file containing the aerodynamic loads extracted from an extensive CFD campaign (174 simulations, at varying speeds, angles of attack and sideslip angles) for a full 3D bill-body-wing-tail configuration of a grey-headed albatross in steady gliding flight.